The Representation of Women in Li Young-Lee’s Poems - Patricia Vania Septhine Yulia Asthereni (IAIN MADURA, 2020)
Patriarchy has become the central attention of feminism because its practices expand to many different fields in society, such as politics, law, power relations between male and female and literary works, such as poems. Lee, as a poet with a lot of notable achievements, also internalises his patriarchal ideology through the women representation portrayed in